Harmony of Senses – 3D Documentaries of Herzog and Wenders - Turnacker Katalin (Acta Universitatis Sapientiae: Film and Media Studies, 2014)
The two still active great artists of the new German cinema, Werner Herzog and Wim Wenders, presented their 3D documentaries on the 2011 Berlinale. This coincidence, not to be neglected in itself, is more than a mere experimentation with the new technology. Indeed, it much rather reveals the complexity of perceptions coming into action during the film experience and their relationship with the onlooker. It highlights the process in which the viewer involuntarily, thoughtlessly relates to their own sensory experience. Following their feature films grounded on the visuality of the cinema experience indicative of the German New Wave, the two directors now created a documentary which draws on the synthesis of various senses and a viewer’s position focusing on perception and interpretation. This paper proposes to analyze how the harmony of senses happens on various levels, from the application of visible, audible, tangible subject motifs and modes of expression asking for various forms of perception, and all the way to the directorial perspective focusing on the viewer’s engagement.